Confusions of meaning in the concept of place: an investigation into the role place occupies in influencing the production and reception of the artwork - Sneddon, Andrew Graeme (The University of Edinburgh, 2018)
This practice-led research examines ideas surrounding the interpretation of place; the representation and experience of place are explored in my practice and throughout the thesis. The practice and thesis develop an interdependent relationship where one informs the other and each provides a critical platform whereby existing beliefs are brought into question and new ideas emerge. During the research period the practice is tested against different circumstances in a variety of situations and novel responses are generated. The thesis critically analyses approaches to interpreting place through a number of formats and a variety of sources. Both practice and theory are examined through peer-reviewed conference papers, artist-in-residence programmes and publications allowing new ideas to be explored and scrutinized by the academy. A working method that recognizes the importance and usefulness of serendipity and sagacity is established, bringing together my practice and the theoretical scope of the research. My primary focus is to understand and develop critical responses to the experience and representation of place within the realm of contemporary art practice. The work of W.G. Sebald and the secondary literature surrounding his work plays a significant role in providing ways of dealing with the entanglement of knowledge. Period Drama is both the name of an artwork and the name I have given to a conference paper. Both explore the convoluted and complex methods involved in realizing a site-specific work that challenges fiercely-held beliefs about place. My intention throughout the research has been to examine a variety of approaches that explore the representation and experience of place within contemporary art practice. Prominent within this examination has been the highlighting of the need to belong to a particular place and the sense of displacement generated when this need to belong is challenged or the nature of this connection is questioned.
Keywords: place and space; contemporary art; site-responsive; W.G. Sebald; Edward Casey; David Harvey